Association of frailty with long-term homecare utilization in older adults following cancer surgery: Retrospective population-based cohort study. Issue 4 (April 2021) - Chesney, Tyler R.; Haas, Barbara; Coburn, Natalie; Mahar, Alyson L.; Davis, Laura E.; Zuk, Victoria; Zhao, Haoyu; Wright, Frances; Hsu, Amy T.; Hallet, Julie
Abstract: Introduction: Frailty is an important prognostic factor, and the association with postoperative dependence is important outcome to older adults. We examined the association of frailty with long-term homecare utilization for older adults following cancer surgery. Methods: In this population-based cohort study, we determined frailty status in all older adults (≥70 years old) undergoing cancer resection (2007–2017). Outcomes were receipt of homecare and intensity of homecare (days per month) over 5 years. We estimated the adjusted association of frailty with outcomes, and assessed interaction with age. Results: Of 82, 037 patients, 6443 (7.8%) had frailty. Receipt and intensity of homecare was greater with frailty, but followed similar trajectories over 5 years between groups. Homecare receipt peaked in the first postoperative month (51.4% frailty, 43.1% no frailty), and plateaued by 1 year until 5 years (28.5% frailty, 12.8% no frailty). After 1 year, those with frailty required 4 more homecare days per month than without frailty (14 vs 10 days/month). After adjustment, frailty was associated with increased homecare receipt (hazard ratio 1.40; 95%CI 1.35–1.45), and increasing intensity each year (year 1 incidence rate ratio [IRR] 1.22, 95%CI 1.18–1.27 to year 5 IRR 1.47, 95%CI 1.35–1.59). The magnitude of the association of frailty with homecare receipt decreased with age ( p interaction <0.001). Conclusion: While the trajectory of homecare receipt and intensity is similar between those with and without frailty, frailty is associated with increased receipt of homecare and increased intensity of homecare after cancer surgery across all age groups.